2022
DOI: 10.7554/elife.72031
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally sensitive hotspots in the methylome of the early human embryo

Abstract: In humans, DNA methylation marks inherited from gametes are largely erased following fertilisation, prior to construction of the embryonic methylome. Exploiting a natural experiment of seasonal variation including changes in diet and nutritional status in rural Gambia, we analysed three datasets covering two independent child cohorts and identified 259 CpGs showing consistent associations between season of conception (SoC) and DNA methylation. SoC effects were most apparent in early infancy, with evidence of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 90 publications
(205 reference statements)
0
15
0
Order By: Relevance
“…Maintenance of parent of origin-specific methylation (PofOm) in the pre-implantation embryo is critical for genomic imprinting ( 71 ), and several previously identified SIV loci have been found to be associated with imprinted genes and/or PofOm ( 25 , 27 , 57 ). 58 hvCpGs (1.4%) were annotated to 32 imprinted genes ( Supplementary Table S13 ), no more than expected by chance since 1.9% of array background CpGs are annotated to imprinted genes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Maintenance of parent of origin-specific methylation (PofOm) in the pre-implantation embryo is critical for genomic imprinting ( 71 ), and several previously identified SIV loci have been found to be associated with imprinted genes and/or PofOm ( 25 , 27 , 57 ). 58 hvCpGs (1.4%) were annotated to 32 imprinted genes ( Supplementary Table S13 ), no more than expected by chance since 1.9% of array background CpGs are annotated to imprinted genes.…”
Section: Resultsmentioning
confidence: 99%
“…We explored whether hvCpGs show sensitivity to pre-natal environment by examining their overlap with loci associated with season of conception (‘SoC’) in a rural Gambian population exposed to seasonal fluctuations in diet and other factors ( 77–79 ). hvCpGs comprise 70 (29%) out of 242 previously identified SoC-CpGs ( 57 ) overlapping array background, an approximately 3-fold enrichment relative to distribution-matched controls ( Supplementary Table S11 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The precision and the timing of such processes are pivotal for avoiding developmental defects or embryonic lethality, as an incorrect establishment of the embryonic epigenome would cause a defective zygotic genome activation (ZGA). Such a brief but crucial phase represents a window of vulnerability towards interfering maternal and environmental factors (such as chronic metabolic disorders, polycystic ovary syndrome, diet, and teratogen exposure), as highlighted by an ever-increasing number of studies [68][69][70][71]. In particular, it has been suggested that the association between assisted reproductive treatment (ART) procedures and slightly higher frequences of imprinting syndromes may be due to ART causing an abnormal epigenome in the offspring [71].…”
Section: Fertilization and Early Embryo Developmentmentioning
confidence: 99%